Success factors of overall improvement of microenterprises in Malaysia: an empirical study - Alom, Fardous; Abdullah, Moha Asri; Moten, Abdul Rashid; Azam, Ferdous (Springer, 2016)
Most of the enterprises of the World belong to the class of microenterprises and thus, the contributions of icroenterprises to the national economic growth and development of the ountries are not ignorable. Establishing a microenterprise does not involve the huge formalities and substantial funds that small, medium and large enterprises require. However, for a healthy growth of microenterprises, the determining factors must be identified and policies should be undertaken and implemented in an appropriate manner. The objective of the current study is to identify different potential factors that contribute to the overall growth of the Malaysian microenterprises. Computing descriptive statistics and applying multiple regression analysis to data for 253 microenterprises of Malaysia, the study finds that a certain number of entrepreneurial and enterprise characteristics along with several economic factors affect the overall performance of microenterprises. Specifically, it is found that competition and the age of the enterprises negatively affect overall performance of the microenterprises whereas age of the entrepreneurs, education, business training, demand for the product/service, availability of physical space for business expansion in the city area, availability of financing and sufficiency of secured amount of finance pose positive impacts on the growth. The results of this study provide some insights to policymakers and business practitioners to address the determinants pertaining to microenterprise growth